Cardiovascular Outcomes with Sotagliflozin - Baglioni, Piero; Marchand, Lucien; Villar, Emmanuel; Green, Lisa; Bhatt, Deepak L; Steg, P. Gabriel; Pitt, Bertram (The New England journal of medicine, 2021)
To the Editor: In the SOLOIST-WHF trial (Effect of Sotagliflozin on Cardiovascular Events in Patients with Type 2 Diabetes Post Worsening Heart Failure), Bhatt et al. (Jan. 14 issue) 1 report that death from cardiovascular causes and hospitalizations and urgent visits for heart failure (the composite primary outcome) occurred in fewer patients in the sotagliflozin group than in the placebo group. This benefit was also seen in the SCORED trial (Effect of Sotagliflozin on Cardiovascular and Renal Events in Patients with Type 2 Diabetes and Moderate Renal Impairment Who Are at Cardiovascular Risk) reported by Bhatt et al. (also in Jan. . . .